Investigating the Influence of Education on Political Behavior in the 2024 Presidential Election: A Study of North Sumatra Province - Ilham Bagaskara; Hertaty Rajagukguk (IHSA Institute, 2024)
The 2024 Presidential General Election in North Sumatra Province serves as a critical juncture for exploring the intricate relationship between education and political behavior. By utilizing a mixed-methods approach, this study aims to examine the influence of education on political choices among voters in the province. Through stratified random sampling and a structured survey instrument, quantitative data were collected on participants' educational background, political attitudes, preferences, and voting behavior. Additionally, in-depth interviews provided qualitative insights into the mechanisms through which education shapes political choices. The statistical analyses revealed a statistically significant positive relationship between higher levels of education and more liberal political attitudes and voting behavior. The qualitative findings highlighted the role of critical thinking skills, exposure to diverse perspectives, and access to information as factors shaping political preferences among individuals with higher levels of education. Conversely, participants with lower levels of education cited traditional values, community norms, and family influences as important determinants of their political preferences. These findings underscore the importance of education in promoting democratic participation, informed decision-making, and social progress. The study's implications extend beyond the 2024 Presidential General Election in North Sumatra Province, emphasizing the need for initiatives aimed at improving educational opportunities and promoting informed citizenship.